Perinatal risk factors for late neonatal severe acute kidney injury in very low birth weight infants: a retrospective study - Kim, Hyun Ho; You, Jihye; Park, Esther; Kim, Jin Kyu (Frontiers in Pediatrics, 2024)
This study aimed to identify the perinatal risk factors of severe acute kidney injury (AKI) occurring after the first week of birth in very low birth weight (VLBW) infants who survived up to the first week. We conducted a single-center, retrospective cohort study on VLBW infants (birth weight, <1500 g) delivered at <32 weeks of gestational age (GA) from January 2012 to December 2022. We classified AKI based on changes in serum creatinine and urine output based on the modified The Kidney Disease: improving Global Outcomes (KDIGO) neonatal AKI criteria. Stage 2-3 AKI were considered as severe AKI (sAKI). We performed logistic regression analysis to evaluate risk factors for late neonatal severe AKI identified in the second week after birth. We included 274 VLBW infants. The prevalence of late neonatal severe AKI (sAKI) was 27.4%, with the diagnosis rate of sAKI being higher early after birth. Logistic regression analysis revealed that the factors associated with late neonatal sAKI were small for gestational age (SGA) (OR, 3.02; P = 0.032), endotracheal intubation in the delivery room (OR, 2.79; P = 0.022), necrotizing enterocolitis (NEC) (OR, 12.41; P = 0.029), and decreased minimum weekly fluid balance <0 (OR, 2.97; P = 0.012). SGA, intubation in the delivery room, and NEC were associated factors for late neonatal sAKI in VLBW infants. The association of no weekly weight gain with increased late neonatal sAKI risk indicates its use in guiding fluid therapy and aids in biomarker research.